Catalytic oxidation of high-concentration CO over La0.9M0.1CoO3 (M = Ce, Sr) facilely promoted by glucose. (26th October 2021) - Teng, Zihao; Yun, Jianyu; Du, Libin; Huang, Junqin; Hao, Qinglan; Dou, Baojuan; Hui, Kwun Nam; Bin, Feng
Abstract : Addition of glucose and introduction of Ce/Sr into LaCoO3 can create more oxygen vacancies and Co 3+ active sites, facilitating the catalytic activity for CO oxidation. Abstract : Glucose-free and glucose-containing LaCoO3 (-G), La0.9 Sr0.1 CoO3 (-G), and La0.9 Ce0.1 CoO3 (-G) perovskite catalysts were synthesized via the sol–gel method, over which the oxidation performance of high-concentration CO was investigated. The experimental results indicate that the catalytic activity can be improved by facilely adding glucose during the preparation where glucose creates a reducing atmosphere and takes away the oxygen atoms of perovskites to form more oxygen vacancies and Co 3+ . CO self-sustained combustion is favorably achieved and La0.9 Ce0.1 CoO3 -G shows the best catalytic performance. Combining the XPS, H2 -TPR, O2 -TPD and CO-TPD results, the outstanding performance of La0.9 Ce0.1 CoO3 -G is mainly ascribed to the relatively higher concentrations of Co 3+, Ce 3+ and oxygen vacancies. The reaction was found to follow the Langmuir–Hinshelwood (L–H) mechanism by in situ IR spectroscopy and kinetic results. Furthermore, La0.9 Ce0.1 CoO3 -G exhibits good high-temperature durability with unchanged CO conversion of 100% at 760 °C. It is suggested that the addition of glucose and the impregnation of Sr or Ce in perovskites is a feasible strategy to design industrial catalysts for CO self-sustained combustion.